Stage Dialectics: Performativity, Thought, and The Novel. - Weaver, Daniel A. (Tufts Archival Research Center, 2017)
Modern’ and ‘Post-modern’ texts (Ulysses, Infinite Jest) take the question of self-hood and turn on its impossibility. Logics of interiority in the theatre and the novel indulge our sense of authority as readers – that our knowledge of character’s thoughts grants us a definitive knowledge of who they are – what they want and why, the constitution of their psychology and a coherent sense of a whole self which we can hold up, as if in a mirror, to some complete version of ourselves. The duplicity of theatre in soliloquy, Shakespeare’s rendition of thought as speech, produces our faith in the definitive interior, the ability to know thyself, only to follow fast upon with the tragic impossibility of ever realizing that self by performing it either to ourselves or others. The questions these texts raise with regards to self-hood should trouble our belief in our ability to know ourselves, and have us ask whether our immediate proximity to the theatre of our own minds grants us privileged self-knowledge or disorienting incoherence.